2018
DOI: 10.1177/1534734618795593
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Novel Super-Oxidized Solution on Top of Standard Treatment in the Home Care Management of Postsurgical Lesions of the Diabetic Foot Reduces Reinfections and Shortens Healing Time

Abstract: The diabetic foot is a very complex and challenging disease involving the lower limb of 8 to 10 million people around the world. 1 Its prevalence has dramatically increased in recent years, leading to significant loss of quality and years of life of the affected patient and creating a dramatic need for effective therapeutic answers. 2 Furthermore, 12% to 15% of overall diabetes costs are due to diabetic foot syndrome, and this percentage increases in developed countries up to 40%. 3 While pathogenetic mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…A single study of a silver based dressing 23 that reported this outcome also showed an increase in the number of infections in the intervention group although no between group statistical analysis was presented with this result. A single study comparing superoxidised solution to a control 30 reported significantly lower rates of reinfection in the intervention arm, but this study was at high risk of bias.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…A single study of a silver based dressing 23 that reported this outcome also showed an increase in the number of infections in the intervention group although no between group statistical analysis was presented with this result. A single study comparing superoxidised solution to a control 30 reported significantly lower rates of reinfection in the intervention arm, but this study was at high risk of bias.…”
Section: Resultsmentioning
confidence: 75%
“…A study comparing a superoxidised solution to standard of care also reported on time to healing 30 . Despite there being no difference in complete wound healing overall at 6 months, time to healing was apparently significantly shorter by a mean of 82 days in the intervention arm compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Rationale: We found 12 studies 27–38 evaluating anti‐septic or antimicrobial dressings or topical antiseptic applications. Five evaluated the use of silver impregnated dressings in comparison with usual care 27–30,37 but all were considered at high or moderate risk of bias.…”
Section: Recommendationsmentioning
confidence: 99%
“…The AOS was found to have broad-spectrum microbicidal activity, and was neither toxic nor sensitizing to skin, mucosal membranes, or eyes. ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical reports have demonstrated the efficacy of AOS formulation 1 when incorporated into the management of chronic wounds, with improved clinical outcomes following both inpatient and outpatient treatment ( 9 11 ). Low pH, hypochlorous acid, and high redox potential account for the broad-spectrum activity of AOS against microorganisms, including M. ulcerans , which is able to survive harsh decontamination procedures ( 16 ).…”
Section: Introductionmentioning
confidence: 99%